Is it Time to Normalize Scapular Dyskinesis? The Incidence of Scapular Dyskinesis in Those With and Without Symptoms: a Systematic Review of the Literature - Paul A. Salamh; William J. Hanney; Trey Boles; Daniel Holmes; Alex McMillan; Austin Wagner; Morey J. Kolber (North American Sports Medicine Institute, 2023)
# Background Up to 67% of adults experience shoulder pain in their lifetime. Numerous factors are related to the etiology of shoulder pain, one of which is thought to be scapular dyskinesis (SD). Given the prevalence of SD among the asymptomatic population a concern is that the condition is being medicalized (clinical findings suggested to require treatment but is ultimately a normal finding). Therefore, the purpose of this systematic review was to investigate the prevalence of SD among both symptomatic and asymptomatic populations. # Methods A systematic review of the literature up to July of 2021. Relevant studies identified from PubMed, EMBASE, Cochrane and CINAHL were screened utilizing the following inclusion and exclusion criteria; inclusion: (a) individuals being assessed as having SD, including reliability and validity studies (b) subjects aged 18 or older; (c) sport and non-sport participants; (d) no date restriction; (e) symptomatic, asymptomatic, or both populations; (f) all study designs except case reports. Studies were excluded if: (a) they were not published in the English language; (b) they were a case report design; (c) the presence of SD was part of the studies inclusion criteria; (d) data were not present distinguishing the number of subjects with or without SD; (e) they did not define participants as having or not having SD. Methodological quality of the studies was assessed utilizing the Joanna Briggs Institute checklist. # Results The search resulted in 11,619 after duplicates were removed with 34 studies ultimately retained for analysis after three were removed due to low quality. A total of 2,365 individuals were studied. Within the studies for the symptomatic athletic and general orthopedic population there were 81% and 57% individuals with SD, respectively, and a total of 60% among both symptomatic groups (sport and general orthopedic population). Within the studies for the asymptomatic athletic and general population there were 42% and 59% individuals with SD, respectively, and a total of 48% among both asymptomatic groups (sport and general orthopedic population). # Limitation A strict inclusion and exclusion criteria was used to identify studies that provided the appropriate data for the purpose of this study. There was a lack of consistency for measuring SD across studies. # Conclusion A considerable number of individuals with shoulder symptoms do not present with SD. More revealing is the number of asymptomatic individuals who do present with SD, suggesting that SD may be a normal finding among nearly half of the asymptomatic population. # Level of Evidence 2a